Controlled shock shells and intracluster fusion reactions in the explosion of large clusters - Peano, F.; Fonseca, R. A.; Martins, J. L.; Silva, L. O. (Physical Review A - Atomic, Molecular, and Optical Physics, 2006)
The ion phase-space dynamics in the Coulomb explosion of very large (similar to 10(6)-10(7) atoms) deuterium clusters can be tailored using two consecutive laser pulses with different intensities and an appropriate time delay. For suitable sets of laser parameters (intensities and delay), large-scale shock shells form during the explosion, thus highly increasing the probability of fusion reactions within the single exploding clusters. In order to analyze the ion dynamics and evaluate the intracluster reaction rate, a one-dimensional theory is used, which approximately accounts for the electron expulsion from the clusters. It is found that, for very large clusters (initial radius similar to 100 nm), and optimal laser parameters, the intracluster fusion yield becomes comparable to the intercluster fusion yield. The validity of the results is confirmed with three-dimensional particle-in-cell simulations.